Unveiling the Thermotolerance and Growth-Promoting Attributes of Endophytic Bacteria Derived from Oryza sativa: Implications for Sustainable Agriculture - Wonder Nathi Dlamini; Wei-An Lai; Wen-Ching Chen; Fo-Ting Shen (Microorganisms)
High temperatures pose significant challenges to rice plants’ growth and their associated endophytic bacteria. Understanding how these bacteria respond to heat stress is vital. We assessed the potential of five endophytic bacterial strains derived from Oryza sativa—Bacillus tequilensis LB3, B. coagulans LB6, B. paralicheniformis AS9, B. pumilus LB16, and B. paranthracis i40C—to mitigate heat stress effects on rice plants. These strains demonstrated robust abilities in producing indole-3-acetic acid (IAA) and siderophores, nitrogen fixation, and solubilization of phosphate and potassium. Under high-temperature conditions, they significantly enhanced rice plant growth, with increases in plant length of up to 78% at 40 °C. Notably, LB6 showed the highest biomass increase (195%). The strains also improved chlorophyll SPAD values, an indicator of reduced heat stress effects and improved plant health. Phytohormone profiling and biochemical analyses revealed significant increases in abscisic acid (ABA) levels, reduced lipid peroxidation (MDA), and elevated osmoprotectant proline accumulation under heat stress. Inoculated plants exhibited up to 539 ng g−1 of ABA (vs. 62 ng g−1 in uninoculated controls), a 68% reduction in MDA (indicating less oxidative damage), and enhanced proline synthesis, collectively suggesting improved stress adaptation. These changes were linked to bacterial IAA production and nutrient modulation, which alleviated heat-induced physiological decline. These findings underscore the potential of these endophytes as biofertilizers to improve rice resilience under heat stress. Among the strains, LB6 exhibited superior performance, offering the greatest promise for heat-stress mitigation in rice production. This study advances our understanding of phytohormonal, heat stress signaling, and chemical processes underlying bacterial-mediated thermotolerance, providing a foundation for sustainable agricultural strategies. Future research can explore morphological and biochemical analyses, stress-responsive gene expression (e.g., HSPs, DREBs, and APX) linked to thermotolerance, and the combined effects of selected strains with fertilizers in high-temperature rice cultivation.